PENGARUH PENAMBAHAN SILASE DAUN SINGKONG DAN MINERAL MIKRO ORGANIK DALAM RANSUM BERBASIS LIMBAH KELAPA SAWIT TERHADAP KECERNAAN SERAT KASAR DAN PROTEIN KASAR - Eko Prasetyo Purba, Erwanto, dan Liman (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2017)
The objectives of this research were to determine: 1) the effect of cassava leaves silage addition in feed based on palm oil waste to digestibility of crude fiber and crude protein; 2) the effect of cassava leave silages and micro organic mineral addition in feed based on palm oil waste to digestibility of crude fiber and crude protein. The research was conducted in Mei—July 2016 in the Cattle and Laboratory of Nutrition and Feed Livestock, Department of Animal Husbandry, Faculty of Agriculture, University of Lampung. This study used a Randomized Block Design (RBD). Treatment used are R0 control diet, R1 addition of 10% cassava leaves silage, R2 addition of 10% of cassava leaves silage and micro organic mineral (Zn 40 ppm, Cu 10 ppm, Se 0,10 ppm, Cr 0,30 ppm). Data were analyzed by Analysis of Varians and continued with Least Significant Difference Test (LSD) 0.05 and 0.01. The result showed that the addition of 10% cassava leaves silage in feed based on palm oil waste no giving a significant result (P<0.05) to digestibility of crude fiber, where as significant effect on crude protein. The addition of 10% cassava leaves silage and micro organic mineral in feed based on palm oil waste also giving a significant result (P<0.05) to digestibility of crude fiber and crude protein. Keywords: Cassava Leaves Silage, Micro Organic Mineral, Palm Oil Waste, Digestibility